The Bride and Groom of the “Canticum novum” - Hodne, Lasse (Acta ad archaeologiam et artium historiam pertinentia, 2017)
The article concentrates on the “Coronation of the Virgin” in medieval art. This image is based on the Bride and Groom theme from the Canticles. However, whereas this text from the Old Testament was examined already by the Church Fathers in their exegetical writings, a “canonical” representation of it was coined only in the 12th century. This “late introduction” reflects deeply rooted changes in religious life which profoundly changed church history. The turtle dove which sings in the Canticles is, according to Saint Bernard of Clairvaux, not only a symbol of faithfulness but also of chastity. This chastity must, in turn, be connected with the chastity of the clergy and the development of the idea of celibacy precisely in this period. Hence, the “Coronation”, besides being a symbol of the Church, is also an expression of a precise conception of the Church, namely a body constituted of men who maintain their virginity as brides awaiting the arrival of the Groom.